INOVASI STRATEGI PEMASARAN UNTUK PENETRASI PASAR INDUSTRI ELEKTRONIK DAN OTOMOTIF DI ERA VUCA WORLD - Ayu Ambarwati (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
The electronics and automotive industry market requires new marketing strategy innovations in this VUCA world era. The Covid pandemic has directed a social transformation based on Volatility, Uncertainty, Complexity and Ambiguity abbreviated as VUCA. At the beginning of 2020, the outbreak that hit China quickly spread to various neighboring countries in Asiaand Europe. In just a matter of weeks, the virus infected many countries. The Covid-19 virus pandemic has changed the world order and its impact is very much felt in the business and economic world. The government through the Ministry of Industry (Kemenperin) chose five domestic manufacturing sectors to support national economic growth. Meanwhile, the government's automotive industry has launched various policies or stimuli for this sector. One of the government's efforts to accelerate economic recovery is through the provision of fiscal incentives in the form of reducing sales tax on luxury goods borne by the government (PPnBM) for motor vehicles. The data in the research that we get will be used as analysismaterial, in this case what is needed is Primary Data and Secondary Data. The data we collect is in the form of (1) Literature and field studies by directly knowing the marketing strategies carried out in the field along with the distribution of questionnaires (2) data analysis using the IFAS-EFAS method and the IE matrix. The analysis used is quantitativelywith the help of processing then provided in the form of IFAS-EFAS matrix and IE matrix. Another analysis technique is to use descriptive techniques, namely reading journals, books or other information from previous researchers. The results of the analysis using the IFAS-EFAS matrix and obtained a total internal factor score obtained of 3.50, then internal factorsare included in the high category and external factors the results of the total score obtained are 3.19, then external factors are included in the medium category. From the total IFAS and EFAS obtained, it shows that the position on the IE matrix is in cell I which means Grow and Build